Effects of Ethephon, 1-Aminocyclopropane-1-carboxylic Acid, and Inhibitors of Ethylene Synthesis on the Gravitropically Induced Movement of Mimosa pudica Pulvinus - Roblin, Gabriel (1985)
Primary pulvini of Mimosa pudica L. displaced from their position display gravitropic movements beginning about 15 minutes after their reorientation. Ethephon, an ethylene-releasing compound, and 1-aminocyclopropane-1-carboxylic acid, an intermediate in ethylene biosynthesis, enhance these movements at a concentration as low as 10 nanomolar. Inhibitors of ethylene synthesis (l-α-(2-aminoethoxyvinyl)glycine, (aminooxy)acetic acid, and Co(2+)) reduce the amplitude of the movements. The promotive action of 1-aminocyclopropane-1-carboxylic acid is abolished by l-α-(2-aminoethoxyvinyl)glycine. These results permit one to conclude that ethylene may modify the curvature movement but not the initiation of the gravitropic reaction. With reference to the pulvinus functioning based on turgor variations and ion migrations inside the organ, namely K(+) acting as the osmoticum, the data suggest that ethylene may act by increasing the membrane permeability to water and/or by altering an ion pump.